Dynamika zmian w obszarze pracy a rozwój studiów karierowych - Solarczyk-Ambrozik , Ewa (Studia Edukacyjne, 2018)
The widely accepted definition which relates a career to an individual’s experience acquired during work, places it in the social space and in a specific time. The contextual and individual perspective provides an insight into the interrelationships between individual agency and the limiting or stimulating aspects of the social context. In career studies, it is emphasized that the concept of a career should be related to the category of work, because career is one of the key concepts used in Western societies of the twentieth century to describe the history of work understood as employment, despite the fact that new career theories go beyond this area of reference. The article discusses the development of career studies that reflect the transformation of the work environment. Attention is paid to the dynamic transformations in this environment are a background to changing career patterns and the relevant studies. The genealogical roots of contemporary career theories are shown, with special emphasis ontheir transdisciplinary nature. The article moreover focuses on problem areas inspired by the 1970s, which proved catalytic for modern career studies. The article concludes with reflections on the extent to which changes occurring in the area of work, and in particular experiencing discontinuities, pose a challenge to the fundamental principles and standards on which the theories, research and practices in the field of careers are based.